The Role Of Accounting Education In Promoting Entrepreneurship Sustainability In South Africa - Oladele Musili Folasade; Calvin Mahlaule; Nwosu Lilian Ifunanya (CV. AFDIFAL MAJU BERKAH, 2026)
Re-examining the educational system is necessary, considering the startling number of South African graduates who are observed wandering the streets. The graduates must be equipped with skills that will enable them to support themselves independently. Since graduates have more opportunities for both paid and self-employment, accounting education is crucial. Students can use the abilities they have learned in their future family life and personal lives. It is necessary to acquire the fundamentals of accounting independently to maintain records of commercial activities. In this study, the importance of accounting education to sustainable enterprise was discussed. Accounting ideas such as